2022
DOI: 10.3390/cells11203322
|View full text |Cite
|
Sign up to set email alerts
|

β-COP Regulates TWIK1/TREK1 Heterodimeric Channel-Mediated Passive Conductance in Astrocytes

Abstract: Mature astrocytes are characterized by a K+ conductance (passive conductance) that changes with a constant slope with voltage, which is involved in K+ homeostasis in the brain. Recently, we reported that the tandem of pore domains in a weak inward rectifying K+ channel (TWIK1 or KCNK1) and TWIK-related K+ channel 1 (TREK1 or KCNK2) form heterodimeric channels that mediate passive conductance in astrocytes. However, little is known about the binding proteins that regulate the function of the TWIK1/TREK1 heterod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…To achieve this, we tagged each TREK subfamily protein, TREK1, TREK2, and TRAAK, with GFP, and β-COP was tagged with mCherry to confirm the specificity of their localization. We observed that TREK1 and β-COP co-localized throughout the cell, particularly near the cell membrane, which is consistent with our previous findings [18,29]. Conversely, the co-localization of TREK2 and β-COP was densely localized in a Golgi-like organelle adjacent to the nucleus.…”
Section: Association With β-Cop Differs For Each Member Of the Trek F...supporting
confidence: 92%
See 2 more Smart Citations
“…To achieve this, we tagged each TREK subfamily protein, TREK1, TREK2, and TRAAK, with GFP, and β-COP was tagged with mCherry to confirm the specificity of their localization. We observed that TREK1 and β-COP co-localized throughout the cell, particularly near the cell membrane, which is consistent with our previous findings [18,29]. Conversely, the co-localization of TREK2 and β-COP was densely localized in a Golgi-like organelle adjacent to the nucleus.…”
Section: Association With β-Cop Differs For Each Member Of the Trek F...supporting
confidence: 92%
“…When VN-and VC-tagged proteins bind, the separated Venus fluorescent proteins come close to each other, resulting in clear Venus fluorescence. Similar to previous reports [29], a clear BiFC signal was observed throughout the HEK293T cells co-transfected with VN-β-COP and VC-TREK1. In HEK293T cells cotransfected with VN-β-COP and VC-TREK2, the signals were concentrated in a narrow area near the organelles, similar to the Golgi apparatus.…”
Section: Association With β-Cop Differs For Each Member Of the Trek F...supporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, in this study, NHERF-1 was identi ed as the protein that binds to the N-terminus of TREK-1, next to β-COP. β-COP was identi ed as an interacting protein of TREK-1 in astrocytes, binding to the N-terminal domain and increasing both surface expression and channel activity 29,41 . However, NHERF-1 is bound to the N-terminal domain of TREK-1 but reduces both surface expression and channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…To further determine the binding site of NHERF-1 within TREK-1, the N terminus of TREK-1 was divided into four sections (ΔN1, ΔN1,2, ΔN1,2,3, or ΔN) (Figure S4A) 29 . BiFC signals were detected for TREK-1 ΔN1, TREK-1 ΔN1,2, and TREK-1 ΔN1,2,3 using NHERF-1, but not for TREK-1 ΔN using NHERF-1 (Figure S4B).…”
Section: Identi Cation Of Binding Regions Between Nherf-1 and Trek-1mentioning
confidence: 99%